Ultrasonic instruments and concurrent antithrombotic medication in mastectomy: safe and effective - Tamminen, Anselm; Aaltonen, Riitta I.; Ristola, Marko T. (Springer Science and Business Media LLC, 2025)
BackgroundPostoperative bleeding is one of the most common complications after mastectomy. Antithrombotic medications increase the risk of these complications but discontinuing them may predispose the patient to thromboembolic events. This study aimed to evaluate whether antithrombotic medications can be safely continued perioperatively when ultrasonic instrument is used in surgery.MethodsThe study included all breast cancer patients who underwent mastectomy with an ultrasonic instrument and were on uninterrupted antithrombotic medication during a 12-year study period (2010-2022) at a single university hospital. The medical records were investigated for patients who had concurrent anticoagulant or antiplatelet therapy at the time of surgery. All bleeding complications during the 30 days following surgery were recorded.ResultsIn total 315 mastectomies in 299 patients were performed with three different ultrasonic instruments under concurrent antithrombotic medication. The mean age of the patients was 81 years, and 82% (258 of 299) had an ASA Classification of level 3 or 4. The indications for antithrombotic medication varied, with the most prevalent being cardiac arrhythmia (38%) and previously suffered stroke (14%). Warfarin, acetylsalicylic acid (aspirin), and direct oral anticoagulants (DOAC) each accounted for approximately a quarter of the studied patients. Bleeding complications were observed in five cases (1.6%, 5/315) during the 30-day postoperative period. Three patients underwent re-operation. None of the patients underwent reoperation on the day of the mastectomy, and in only one patient the need for reoperation was directly associated with the mastectomy procedure. In the other two patients the bleeding complications were preceded by seroma puncture and a drainage issue. The results indicate a low incidence rate of postoperative bleeding despite the continuation of antithrombotic medication when an ultrasonic instrument is utilized in the operation.ConclusionThe utilization of ultrasonic instruments in mastectomy permits safe continuation of antithrombotic medications, thereby reducing the risk of thromboembolic events and streamlining surgical preparation.